How we use molecular minimal residual disease (MRD) testing in acute myeloid leukaemia (AML). (15th October 2020) - Dillon, Richard; Potter, Nicola; Freeman, Sylvie; Russell, Nigel
Summary: In recent years there have been major advances in the use of molecular diagnostic and monitoring techniques for patients with acute myeloid leukaemia (AML). Coupled with the simultaneous explosion of new therapeutic agents, this has sown the seeds for significant improvements to treatment algorithms. Here we show, using a selection of real‐life examples, how molecular monitoring can be used to refine clinical decision‐making and to personalise treatment in patients with AML with nucleophosmin ( NPM1 ) mutations, core binding factor translocations and other fusion genes. For each case we review the established evidence base and provide practical recommendations where evidence is lacking or conflicting. Finally, we review important technical considerations that clinicians should be aware of in order to safely exploit these technologies as they undergo widespread implementation.